Additively manufactured ultrafine grained Aermet100 with superior mechanical property - Yanwen Liang; Jie Liu; Xiaotian Zhang; Yonghao Weng; Sheng Zhong; Tiannan Li; Peng Zhang; Chunpan Yang; Ying Xing; Jiazhe Fu; Kehong Wang (Journal of Materials Research and Technology)
In this study, Aermet100 high-strength steel was fabricated using laser powder bed fusion (LPBF) technology. The influence of various process parameters on the surface quality and relative density of the samples was systematically examined. Additionally, the effects of the heat treatment process on the microstructure and mechanical properties of the material was investigated. The results indicate that the specimens were well-formed, achieving a relative density of 99.99% through an optimal combination of process parameters: a laser power of 220 W, scanning speed of 1000 mm/s, scanning rotation of 67°, and hatch spacing of 0.07 mm.The additively manufactured Aermet100 specimens exhibited ultrafine grains with an average size of 0.4 μm. Tempering of the as-built specimens at 482 °C for 2 h resulted in the highest strength and hardness. Grain refinement is identified as the primary factor contributing to the excellent combination of strength and ductility. Moreover, precipitation of secondary strengthening phases is attributed to hindering the movement of dislocations. The combined effects of fine grain strengthening, dislocation strengthening, and precipitation strengthening ultimately result in significant improvements in strength, reaching a maximum of 2064 MPa and an elongation of 8%.